Implementation of the Fisher-Yates Shuffle Game Algorithm in Learning Hijaiyah Letters - Alvien Muhammad Kannabi; Norhikmah M.Kom (SCOPUS ID: 57216417658) (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
In 2020 the Indonesian government and the world health agency (WHO) declared the Covid-19 virus a pandemic. As a result, some activities cannot be carried out offline, especially in learning activities. The government requires that learning activities be carried out online or online. The number of children who really need help to understand the learning material provided, for example, is a game which is one of the media in learning for children to make it more interesting in its delivery. With the aim of providing basic Koran education for early childhood with interactive and fun games and the application of the Fisher-Yates Shuffle algorithm in the quiz feature that is used to randomize hijaiyah letter questions. Stages of research 1). Collecting data using library studies, namely Iqra books and related research papers. 2). Game design using story board. 3). Application of the Fisher-Yates Shuffle algorithm. 4). Testing the Fisher-Yates algorithm, black box and question. The results obtained from 10 question and 96 respondents resulted in 89.5% concluding that the hijaiyah letter game uses the Android-based Construct 2 game engine. implementation of the Fisher-Yates Shuffle algorithm on the quiz feature is feasible to use.